Bronchiolitis of Infancy Discharge Study (BIDS): a multicentre, parallel-group, double-blind, randomised controlled, equivalence trial with economic evaluation - Steve Cunningham (Health Technology Assessment, 2015)
Background: There are no randomised trials of peripheral capillary oxygen saturation (SpO2) targets in acute respiratory infection. Two national guidelines recommended different targets for the management of acute viral bronchiolitis. Objectives: To compare the American Academy of Pediatrics guideline target of SpO2 ≥ 90% with the Scottish Intercollegiate Guidelines Network target of SpO2 ≥ 94%. Design: A multicentre, parallel-group, double-blind, randomised controlled, equivalence trial with economic evaluation. Setting: Eight paediatric hospital departments in the UK. Participants: Infants > 6 weeks and ≤ 12 months of age (corrected for prematurity) with physician-diagnosed bronchiolitis admitted to hospital from a paediatric emergency assessment area. Follow-up for 6 months by standardised telephone contacts. Intervention: Infants were randomised to a target oxygen saturation of ≥ 94% (standard care) or ≥ 90% (modified care) displayed by a pulse saturation oximeter (Masimo Corporation Limited, CA, USA). Routine care: All infants received routine care in addition to the study intervention. Infants were eligible for discharge when they exhibited a SpO2 of ≥ 94% in room air for 4 hours including a period of sleep and were also feeding adequately (≥ 75% usual volume). Primary outcome: A total of 615 infants were recruited, of whom 308 were allocated to the standard care group and 307 to the modified care group. The primary outcome was time to cough resolution. There was equivalence at the prespecified variance of ± 2 days [time to cough resolution: standard care group, 15 days; modified care group, 15 days; median difference 1 day (benefit modified), 95% confidence interval (CI) –1 to 2 days]. Secondary results: Return to adequate feeding occurred sooner in infants in the modified care group than in those in the standard care group (19.5 vs. 24.1 hours). This difference was non-equivalent [median difference 2.7 hours (95% CI –0.3 to 7.0 hours) versus prespecified ± 4 hours; post-hoc hazard ratio 1.22 (95% CI 1.04 to 1.44 (p-value = 0.015)]. Parent perspective of the time taken to return to normal was not equivalent, being 12 days in the standard care group compared with 11 days in the modified care group [median difference 1.0 day (95% CI 0.0 to 3.0 days) versus prespecified ± 2 days; post-hoc hazard ratio 1.19 (95% CI 1.00 to 1.41); p-value = 0.043]. At 28 days, SpO2 was equivalent [mean difference 0.11% (95% CI –0.35% to 0.57%), within the 1% prespecified]. The modified care group (55.6%) required oxygen less than the standard care group (73.1%), and for a shorter period (5.7 hours vs. 27.6 hours). Infants in the modified care group were fit for discharge (30.2 hours vs. 44.2 hours, hazard ratio 1.46, 95% CI 1.23 to 1.73; p-value < 0.001) and were discharged (40.9 hours vs. 50.9 hours; hazard ratio 1.28, 95% CI 1.06 to 1.50; p-value < 0.003) sooner than those in the standard care group. There were 35 serious adverse events in the standard care group, compared with 25 in the modified care group. Eight infants in the standard care group and 12 in the modified care group were admitted to a high-dependency unit. By 28 days, 23 infants had been readmitted to hospital in the standard care group and 12 infants in the modified care group. Parents of infants in the modified care group did not experience higher levels of anxiety and, by 14 days, had lost 28% fewer hours to usual activities. NHS costs were £290 lower in the modified care group than in the standard care group, with additional societal costs also being lower in the modified care group. Conclusions: Management of infants to a SpO2 target of ≥ 90% is as clinically effective as ≥ 94%, gives rise to no additional safety concerns, and appears to be cost-effective. Future work could focus on the safety and effectiveness of using intermittent oxygen saturation monitoring in secondary care, and to consider what are safe and effective oxygen saturation targets for children with bronchiolitis managed in primary care. Trial registration: This trial is registered as ISRCTN28405428. Funding: This project was funded by the NIHR Health Technology Assessment programme. Masimo Corporation Limited, CA, USA, kindly provided oxygen saturation monitors with standard and altered algorithms.